Inclusive single-particle distributions and transverse momenta of forward produced charged hadrons in mu p scattering at 470 GeV - Adams, MR; Aderholz, M; Aid, S; Anthony, P; Averill, D; Baker, MD; Baller, B; Banerjee, A; Bhatti, A; Bratzler, U; Braun, H; Carroll, T; et al. (1997)
Using data from the Fermilab fixed target experiment E665, general properties of forward produced charged hadrons in μp interactions at a primary muon energy of 470 GeV are investigated. The normalized inclusive single-particle distributions for Feynman-x D(xF) and for the transverse momentum D(pt2, xF) are measured as a function of W and Q2. The dependence of the average transverse momentum squared 〈pt2〉 on xF, W and Q2 is studied. The increasing contribution from diffractive production as Q2 decreases leads to a reduction of the average charged hadron multiplicities at low (positive) xF and an enhancement at large xF, for Q2 ≲ 10 GeV2. It also reduces 〈pt2〉 for Q2 ≲ 5 GeV2 and 0.4 ≲ xF < 1.0. © Springer-Verlag 1997.